The experience of use of the sand art-therapy with children with autism spectrum disorders - Kotlovanova, O.V.; Malinina, E.V. (Autizm i narušenie razvitiâ, 2015)
The article presents the results of effective work to use sand art-therapy for treatment of behavior problems in children with autism spectrum disorder. The article describes the session plan, children's behavior in dynamics and intermediate results of work with children with autism spectrum disorders in the framework of this program. The influence of the sand art-therapy on the children's behavior was analyzed. The clinical case of sessions with the boy K. was described. The overwhelmingly positive influence of such sessions was determined. Представлены результаты эффективной работы по использованию песочной арт-терапии при коррекции поведения у детей с расстройствами аутистического спектра. Описан ход занятий, поведение детей в динамике и промежуточные результаты работы с детьми с расстройствами аутистического спектра по данной программе. Проанализировано влияние песочной арт-терапии на поведение ребят. Описан клинический пример занятий с мальчиком К. Выявлено преимущественно положительное воздействие таких занятий на детей с аутизмом.